2022
DOI: 10.3390/genes13050773
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics Reveals the Diversity and Taxonomy of Carbohydrate-Active Enzymes and Antibiotic Resistance Genes in Suancai Bacterial Communities

Abstract: Suancai, as a traditional fermented food in China with reputed health benefits, has piqued global attention for many years. In some circumstances, the microbial-driven fermentation may confer health (e.g., probiotics) or harm (e.g., antibiotic resistance genes) to the consumers. To better utilize beneficial traits, a deeper comprehension of the composition and functionality of the bacterial species harboring enzymes of catalytically active is required. On the other hand, ingestion of fermented food increases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…(Yasir et al, 2022). Song et al (2022) also reported that the majority of ARGs found in suancai (traditional cabbage pickle) were linked to Pseudomonas, the main genus in raw vegetables. Therefore, it is imperative to implement hygienic handling practices and maintain a clean processing environment to prevent the spread of ARGs and protect the health of consumers.…”
Section: Bloomfield Et Al (2023)mentioning
confidence: 99%
See 1 more Smart Citation
“…(Yasir et al, 2022). Song et al (2022) also reported that the majority of ARGs found in suancai (traditional cabbage pickle) were linked to Pseudomonas, the main genus in raw vegetables. Therefore, it is imperative to implement hygienic handling practices and maintain a clean processing environment to prevent the spread of ARGs and protect the health of consumers.…”
Section: Bloomfield Et Al (2023)mentioning
confidence: 99%
“…Lactic acid bacteria are the predominant species in most fermented vegetables (Liu et al., 2023 ; Yasir et al., 2022 ), with a low abundance of ARGs (Yasir et al., 2022 ). Several metagenomic studies have shown that ARGs related to lincosamides, aminoglycosides, tetracyclines and multidrug resistance are some of the most abundant ARGs in fermented vegetables (Liu et al., 2023 ; Song et al., 2022 ; Yasir et al., 2022 ). Indeed, high levels of ARGs found on fermented vegetables were associated with bacteria related to improper storage and handling of fermented foods, or linked to cross‐contamination from processing environments or equipment, such as in the case of Klebsiella sp.…”
Section: The Resistome Of Food Productsmentioning
confidence: 99%